Hubungan Status Gizidanperkembangan Anak Usia 1-3 Tahun Di Kelurahan Campurejo, Kecamatan Mojoroto, Kota Kediri - Susiani Endarwati; Siti Komariyah (coba, 2017)
Optimal development requires a balanced nutritional intake, especially in children aged 1-3 years (toddler). The role of parents is very important, ranging from providing nutrition, to help toddler achieve mental development and optimal cognition. Less nutrient intake, can result in abnormal toddler nutritional status (less nutrition). As a result, toddler will have problems on the development of toddler. The purpose of this study to determine the relationship of nutritional status and the development of children aged 1-3 years in the village Campurejo, district Mojoroto Kediri. The design of this research is analytical corellation with Cross Sectional research approach. The population of this research is children aged 1-3 years in Campurejo Village Kecamatan Mojoroto Kediri with Simple Random Sampling technique in get sample 52 respondents. The research variables consist of independent variable is Nutritional status of children aged 1 - 3 years and dependent variable is the development of children aged 1-3 years. The research instrument is in the form of Health Toward Card (KMS) and Denver Development Screening Test (DDST). Data were analyzed by Spearman correlation test, data analysis using SPSS v.20 program. Based on the result of research, nutritional status of 52 respondents studied got 23 respondents (44.23%) good nutrition status and 2 respondents (3.85%) malnutrition status. The result of the research is 52 respondents (73.07%) normal development and 2 respondents (3.84%) development of delay, the result of statistical test with Spermean Test obtained the result of Z value 0,590 , H1 accepted means there is a relationship of nutritional status with the development of children aged 1-3 years.